Overexpression of ICAT Inhibits the Progression of Colorectal Cancer by Binding with β-Catenin in the Cytoplasm. (September 2021) - Hu, Jiancong; Wang, Zihan; Chen, Junxiong; Yu, Zhaoliang; Zhang, Jingdan; Li, Weiqian; Lin, Mengmeng; Yang, Xiangling; Liu, Huanliang
Inhibitor of β-catenin and T-cell factor (ICAT) was first found as a polypeptide that blocks β-catenin–TCF interaction. Abundant evidence has shown that ICAT has different functions in diverse cancers' progression. Nevertheless, the roles it plays in colorectal cancer (CRC) have not been described. Here, we documented that ICAT expression was higher in CRC tissue than in the adjacent normal tissue and that prognosis was better in high-ICAT expression patients. The overexpression of ICAT inhibited CRC cell proliferation both in vitro and in vivo. Wnt pathway transcriptional activity was suppressed in the CRC cells with ICAT overexpression, where the CCND1 and MYC expression, which occurs downstream of the Wnt signaling pathway, was inhibited. Co-immunoprecipitation experiments showed that ICAT bound with β-catenin in stable overexpression cell lines; immunofluorescence showed the co-localization of ICAT and β-catenin in the cytoplasm. Overall, our study reveals that ICAT inhibits CRC cell proliferation by binding to cytoplasm-located β-catenin, and prevents its translocation, which results in Wnt signaling pathway inactivation. It may provide a scientific foundation for focusing on ICAT in treatments for CRC.